2003
DOI: 10.1002/bit.10825
|View full text |Cite
|
Sign up to set email alerts
|

Application of multivirus spike approach for viral clearance evaluation

Abstract: Viral contamination is a common risk to continuous cell line-derived biologics. Viral validation is thus required for license applications. Viral validation for chromatography procedures is routinely performed by spiking a model virus into the load material and performing the chromatography procedures at small scale under conditions equivalent to the commercial scale. With traditional cell-based infectivity assays, one can only spike one model virus at one time. Quantitative PCR methods (TaqMan) make it possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The feedstock was then filtered through a 0.22 mm filter and the protein concentration determined by optical density at 280 nm (OD 280 ). Finally, the feedstock pool was multispiked with 1% v/v each of X-MuLV, SV40, and MMV stock solutions (Valera et al, 2003). Small-scale chromatography columns (0.66 cm diameter, Bio-Chem Valve/OmniFit) were packed with either naïve QSFF or SFF resin to 19 cm bed height and were equilibrated with 8 column volumes (CV) of equilibration buffer (25 mM Tris, 50 mM NaCl, pH 8.0) at 0.86 mL/min.…”
Section: Scale Down Anion Exchange Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…The feedstock was then filtered through a 0.22 mm filter and the protein concentration determined by optical density at 280 nm (OD 280 ). Finally, the feedstock pool was multispiked with 1% v/v each of X-MuLV, SV40, and MMV stock solutions (Valera et al, 2003). Small-scale chromatography columns (0.66 cm diameter, Bio-Chem Valve/OmniFit) were packed with either naïve QSFF or SFF resin to 19 cm bed height and were equilibrated with 8 column volumes (CV) of equilibration buffer (25 mM Tris, 50 mM NaCl, pH 8.0) at 0.86 mL/min.…”
Section: Scale Down Anion Exchange Chromatographymentioning
confidence: 99%
“…One important function of the AEX step is its ability to remove putative viral contaminants and impurities. Virus reduction studies investigating AEX conditions have shown the step to be highly effective at removing both enveloped and non-enveloped viruses, consistently achieving log 10 reduction values (LRVs) greater than 4 (Curtis et al, 2003;Norling et al, 2005;Shi et al, 1999bShi et al, , 2004Strauss et al, 2009;Tayot et al, 1987;Valera et al, 2003;Zolton and Padvelskis, 1984). In order to ensure that this unit operation maintains its ability to remove viruses while allowing for further development of the step, it is important to gain an understanding of the mechanisms by which AEX processes remove viruses from mAb feedstocks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HCCFs from six mAbs, and seven CHO cell culture processes (mAb1 has two versions), denoted mAb1a, 1b, and 2 through 6, were used as model process fluids in this report. The same HCCF was used in small scale viral clearance studies, some of which was spiked with X-MuLV and/or other model viruses, such as simian virus type 40 (SV40), murine minute virus (MMV) (Valera et al, 2003). All HCCF samples were either processed fresh or frozen at À608C within a short time after harvest, and were frozen/thawed fewer than three times.…”
Section: Model Process Fluids-harvested Cho Cell Culture Fluidsmentioning
confidence: 99%
“…Certain purification modules, including protein A chromatography, have been observed to reliably remove >2-4 log 10 of large enveloped viruses, including X-MuLV (Lau et al, 1999;Shi et al, 2004;Valera et al, 2003). The mechanism for protein A resin to remove virus is to bind specifically to antibodies (Abs), while allowing viruses to flow through the column (Brorson et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 99%